Sustainable Business Development in Fish Cage Groups Based on Economic, Social and Environmental - Fanji Wijaya; Agus Teny (International Journal of Entrepreneurship and Sustainability Studies, 2022)
A tool that aids companies in exploring new ideas in sustainability-focused business models is the Triple Layer Business Model Canvas (TLBMC). By including an environmental dimension based on a life cycle perspective and a social dimension based on a stakeholder perspective, it increases the canvas's business dimension. We can comprehend how a corporation creates economic, environmental, and social values by taking into account all three aspects of its business model. The TLBMC business model for the Fish Cage Group is presented in this research. The TLBMC enables us to comprehend how OSS uses aspects of stakeholder management and life cycle analysis to develop several types of points linked to fish farmers. In spite of being located in an urban setting, fish farmers needed to convert rivers into productive area, and this study identified research shortages in this area.